The Effectiveness of Handling and Controlling Malaria Cases in Riau Islands Province - Tifani Putri, Aurellia; Darmawan, Eki (Jurnal Ilmu Pemerintahan : Kajian Ilmu Pemerintahan dan Politik Daerah, 2026)
The Riau Islands are one of the provinces contributing to malaria cases in Indonesia, with a cumulative total of 245 malaria cases in 2024 spread across districts/cities. Through Minister of Health Regulation No. 22 of 2022 concerning Malaria Control, the Riau Islands have a benchmark for creating malaria treatment and control programs. This study aims to examine the effectiveness of local government policies in managing and controlling malaria cases in the Riau Islands Province. This study uses a descriptive qualitative approach with data collection using primary and secondary data, which is then analyzed narratively. This study uses the policy effectiveness theory proposed by Nugroho as an analytical tool through five indicators, namely appropriate policy, appropriate implementation, appropriate target, appropriate environment, and appropriate process. The results of the study show that the Riau Islands provincial government still faces many obstacles in managing malaria cases, so that policy implementation is still ineffective. This also has an impact on the slow process of achieving malaria elimination in the Riau Islands.